Minority Language Place-Names: A Practice-Oriented Study of the Establishment of the South Sami Kraapohke in Swedish Lapland. (3rd July 2018) - Edlund, Lars-Erik
Abstract : Implementation of the Swedish minority policy has resulted in the national minority languages having been visualized. But what minority language place-names should be put on road signs together with the Swedish names? This article is focused on the establishment of the Sami toponym for Dorotea in southern Swedish Lapland. The question is, which of the following Sami names should be adopted as the official name: Birjevahne (< Sw. Bergvattnet ), Döörte (< Sw. Dorotea ), or the original South Sami Kraapohke . This practice-oriented study illustrates the problems involved in finding out how Sami names are used in living language. Such problems generally arise when place-names are handed down by small language communities. The establishment of the Sami name Kraapohke illustrates the complicated questions that arise when working with minority language place-names and the identity processes associated with such names.